War and the American Economy - Hugh Rockoff (Rutgers University, Department of Economics, 2005)
To cover fully the economics of war would require encyclopedia unto itself. Here I will provide brief introductions to four questions: (1) to what extent did economic forces cause America's wars, (2) after going to war, how has the United States managed the reallocation of resources, (3) how has the United States financed the reallocation of resources, and (4) what have been the economic legacies of the war.
Keywords: 330; Kriegswirtschaft; Kriegsfolgen; USA